2021
DOI: 10.1108/ihr-10-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of the COVID-19 pandemic on the perceptions and sentiments of tourism employees: evidence from a small island tourism economy in the Caribbean

Abstract: PurposeBuilding on tourism crisis studies and behavioral economics, this study describes a national survey conducted among 439 Aruban tourism and nontourism employees.Design/methodology/approachRegression analysis was subsequently conducted to analyze the relationship between experienced well-being, crisis duration and tourism and nontourism employee sentiments.FindingsThe findings indicate that tourism employee sentiments are generally, and significantly, more negative and their concerns about the future are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…The COVID-19 (declared as a pandemic by WHO, 12 March 2020) significantly impacts the global economic, political, and socio-cultural systems (Peterson and DiPietro, 2021). Health communication strategies and measures (e.g.…”
Section: The Covid-19 and Tourismmentioning
confidence: 99%
“…The COVID-19 (declared as a pandemic by WHO, 12 March 2020) significantly impacts the global economic, political, and socio-cultural systems (Peterson and DiPietro, 2021). Health communication strategies and measures (e.g.…”
Section: The Covid-19 and Tourismmentioning
confidence: 99%
“…Current analyses and discussions on what the future holds for island tourism development and possible tourism paradigm shifts are obviously mostly tentative and speculative. The conclusion of most such research is that, taking into account the effects of the pandemic, climate change, the negative impacts of unsustainable island tourism development, and the need to improve islands' resilience in the face of crises, islands need to focus on developing a greener and more sustainable island tourism [45,49], on domestic tourism [50,51], on developing alternative, nature-based types of tourism experiences [51,52], and on economic diversification [52,53].…”
Section: Postpandemic Island Tourism Developmentmentioning
confidence: 99%
“…However, decisions and developments can still have both positive and negative effects. Therefore, we analyzed the current situation of tourism development in the island during the COVID-19 epidemic environment with risks of infection in terms of economic [1,11,29,30], social [1,38,39], and environmental [14,16,23,41] aspects and from the perspective of different stakeholders by referring to the results of national studies in the literature and the theoretical framework of related studies [1,14,21]. The research framework is shown in Figure 2.…”
Section: Research Process and Frameworkmentioning
confidence: 99%
“…The Cronbach's alpha for the three scales was 0.927, 0.925, and 0.933, respectively, which indicated that the scales had high reliability and could be used for further study. Based on the literature [14][15][16]30,39], an 11-question social dimension questionnaire was developed. The analysis revealed that it had a KMO value > 0.932, a Bartlett's approximate χ 2 value of 4107.088, a degree of freedom (df) of 55, and a significance of 0.000 (p < 0.001), making it suitable for factor analysis.…”
Section: Research Toolsmentioning
confidence: 99%
See 1 more Smart Citation